Method for evaluating self-healing effect of emulsified asphalt cold-recycled mixture added with microcapsules

The void characteristics of the emulsified asphalt cold regenerated mixture were analyzed through CT scanning technology, and its self-healing effect was evaluated, which solved the problem of inaccurate evaluation of the self-healing effect of microcapsules in the prior art, and achieved a more accurate self-healing effect evaluation.

CN119804261APending Publication Date: 2025-04-11GUIZHOU PROVINCE BIJIE HIGHWAY ADMINISTRATION BUREAU +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510038616.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to accurately evaluate the self-healing effect of microcapsules on cracks of emulsified asphalt cold regenerated mixtures, especially on the mesoporous scale, when macroscopic mechanical properties tests are difficult to accurately reflect the self-healing effect of microcapsules.

Method used

The internal void characteristics of the emulsified asphalt cold regenerated mixture were scanned and reconstructed by CT scanning technology. The self-healing effect of microcapsules on the emulsified asphalt cold regenerated mixture was evaluated by the self-healing rate of the average void volume and the self-healing rate of the isolated void ratio.

Benefits of technology

Through the analysis of the void characteristic changes at the meticulous level, the self-healing effect of the emulsified asphalt cold regenerated mixture can be more accurately evaluated, making up for the limitations of macroscopic experiments and providing a more accurate evaluation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236251230000051
    Figure BDA0005236251230000051
  • Figure BDA0005236251230000081
    Figure BDA0005236251230000081
  • Figure FDA0005236251220000021
    Figure FDA0005236251220000021
Patent Text Reader

Abstract

The invention discloses a method for evaluating the self-healing effect of a microcapsule-added emulsified asphalt cold-recycled mixture, solves the problem that the crack self-healing effect of the microcapsule-added emulsified asphalt cold-recycled mixture is difficult to accurately evaluate in a macroscopic mechanical test, and belongs to the technical field of emulsified asphalt cold recycling. The method comprises the following steps: firstly, preparing an emulsified asphalt cold recycled mixture semi-cylindrical test piece added with microcapsules, and prefabricating cracks by adopting a semicircular bending fatigue test; the method comprises the following steps: carrying out CT test on a crack-containing test piece before and after maintenance to obtain CT scanning data, carrying out image processing on a semi-cylindrical test piece after twice scanning, cutting the test piece into a cubic test piece by taking a middle crack expansion area of the test piece as a center, and ensuring that a cut part has no crack; the same treatment mode is adopted to calculate internal void parameters of a test piece subjected to two times of CT scanning, the self-healing rate of the void average volume and isolated void ratio is adopted to evaluate the self-healing effect of the microcapsule emulsified asphalt cold-recycled mixture, and the self-healing effect of the microcapsule emulsified asphalt cold-recycled mixture is evaluated more accurately.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for evaluating the self-healing effect of a microcapsule-added emulsified asphalt cold regeneration mixture, and belongs to the technical field of emulsified asphalt cold regeneration. Background Art

[0002] With the large-scale maintenance and repair of asphalt pavements, a large amount of old recycled asphalt pavement (RAP) is generated, which requires a large amount of land to pile up these waste materials, causing serious damage to the ecological environment. Therefore, how to achieve efficient utilization of RAP materials has attracted more and more attention. The cold recycling technology of asphalt pavement constructed at room temperature not only solves the problem of RAP materials occupying land resources, but also realizes the resource reuse of road materials, which is in line with the current low-carbon and environmentally friendly development concept and has good economic, environmental and social benefits.

[0003] In the application process of cold recycling technology, due to the limitation of mechanical properties of emulsified asphalt, RAP materials and other materials, the cold recycled mixture has poor low temperature crack resistance and is difficult to self-heal after cracks are formed, which seriously affects the road performance and durability of cold recycled pavement and is not conducive to the development and promotion of cold recycling technology. At present, the main method is to prepare modified emulsified asphalt with higher strength and better healing effect to give cold recycled mixture stronger low temperature crack resistance and crack self-healing ability.

[0004] Modification of emulsified asphalt can only improve the mechanical properties of cold recycled asphalt mixture, but it is difficult to give the cold recycled mixture the ability to actively heal cracks. Regarding the active healing of asphalt mixtures, some scholars currently add microcapsules containing regeneration agents to asphalt materials to improve the active healing ability of asphalt materials to cracks. When microcracks are generated in the asphalt pavement during service, the microcapsules can be broken during the crack expansion process, releasing the regeneration agent to fill and heal the cracks and prevent further expansion of the cracks. Therefore, the microcapsule method is an effective method to improve the self-healing ability of asphalt materials.

[0005] At present, when characterizing the self-healing ability of asphalt mixtures, it is considered that asphalt itself has certain mechanical properties, and the related properties will change after asphalt aging. The current evaluation method mainly combines the degree of asphalt aging with the evaluation of the self-healing ability of asphalt mixtures, and analyzes the self-healing ability of asphalt mixtures by comparing multiple mechanical properties of asphalt mixtures before and after self-healing. The above method mainly measures the mechanical properties of asphalt mixtures on a macro scale, but the error of asphalt mixtures during macroscopic mechanical tests is difficult to remove. At the same time, the self-healing of cracks in asphalt mixtures only targets small cracks, and it is difficult to ensure the accuracy of the evaluation of crack self-healing effects through macroscopic mechanical tests.

[0006] On the basis of mechanical tests, we hope to analyze the self-healing effect of cracks in asphalt mixtures at the meso and micro levels. Limited by current technical means, the self-healing effect of asphalt mixtures at the micro level is difficult to characterize through experiments. Therefore, it is considered to evaluate the self-healing effect of cracks in asphalt mixtures from a mesoscopic perspective. CT scanning technology can extract the void characteristics of asphalt mixtures at a mesoscopic level, and it can be considered to characterize the self-healing effect of the mixture by studying the changes in the void distribution characteristics. CT scanning technology can be used to scan and reconstruct the void characteristics inside the mixture, and the healing effect of the mixture can be quantitatively analyzed from the changes in the voids inside the mixture.

[0007] The particle size of the commonly used road microcapsules is currently in the micron level, which is relatively small compared to the scale of the asphalt mixture itself. It is not accurate to characterize the self-healing effect of the microcapsules only by using mechanical properties tests on a macro scale. Therefore, the present invention uses a semicircular bending fatigue test to preform cracks on a semicircular bending specimen of a microcapsule emulsified asphalt cold recycled mixture, and performs curing at room temperature for 24 hours. An X-ray tomography test is used to extract the internal void characteristics of the cold recycled mixture before and after curing. The crack self-healing effect of the microcapsule emulsified asphalt cold recycled mixture is analyzed by comparing the changes in void characteristics before and after curing, providing a new idea for the evaluation of the self-healing effect of the emulsified asphalt cold recycled mixture. Summary of the invention

[0008] The purpose of the present invention is to provide a method for evaluating the self-healing effect of emulsified asphalt cold recycled mixture with added microcapsules. The method solves the problem that the current microscopic microcapsules and macroscopic cold recycled mixtures are too different in scale, and it is difficult to accurately evaluate the self-healing effect of microcapsules on cracks in emulsified asphalt cold recycled mixtures using only macroscopic mechanical properties tests. The self-healing effect of emulsified asphalt cold recycled mixtures can be more accurately evaluated by using the changes in the microscopic void characteristics of the cold recycled mixture before and after curing that match the scale of the microcapsules.

[0009] The technical solution of the present invention is as follows: A method for evaluating the self-healing effect of an emulsified asphalt cold recycled mixture with added microcapsules, firstly preparing a semi-cylindrical specimen of an emulsified asphalt cold recycled mixture with added microcapsules, and prefabricating cracks by a semi-circular bending fatigue test; performing a CT test on the cracked specimen before and after maintenance to obtain CT scanning data, performing image processing on the semi-cylindrical specimen after two scans, and cutting it into a cubic specimen with the crack expansion area in the middle of the specimen as the center to ensure that there are no cracks in the cut portion; calculating the internal void parameters of the specimens scanned twice by the same processing method, and evaluating the self-healing effect of the microcapsule emulsified asphalt cold recycled mixture by using the average void volume and the self-healing rate of the isolated void ratio.

[0010] In the aforementioned method for evaluating the self-healing effect of emulsified asphalt cold recycled mixture with added microcapsules, the specific implementation steps are as follows:

[0011] (1) Prepare Marshall specimens of emulsified asphalt cold recycled mixture, group A and group B, wherein the microcapsule content of Marshall specimens of group A is 0%, and the microcapsule content of Marshall specimens of group B is 5%. Cut each Marshall specimen of group A and group B along the direction perpendicular to the height into a cylindrical specimen, and then symmetrically cut into two semi-cylindrical specimens. Perform incision processing at the middle position of the bottom of the semi-cylindrical specimen to prepare a semi-cylindrical bending specimen with a pre-cut. Perform the first semi-circular bending fatigue test on some of the semi-cylindrical specimens in group A and group B under the stress ratio of 0.25, and obtain the first fatigue life of the specimens of group A and group B when loaded to complete fracture;

[0012] (2) performing a semicircular bending fatigue test on the other semi-cylindrical specimens of group A and group B respectively under the condition of a stress ratio of 0.25, controlling the fatigue life of this semi-circular bending fatigue test to be 60% of the fatigue life of the first semi-circular bending test, thereby prefabricating cracks on the semi-cylindrical bending specimens of group A and group B, and immediately performing the first CT scanning test on the semi-cylindrical specimens with prefabricated cracks to obtain the first set of CT scanning data;

[0013] (3) The scanned semi-cylindrical specimen image was cut by software, and the specimen was cut into a cubic specimen with the crack extension area in the middle of the specimen as the center. During the cutting process, all slices of the cut part were checked to ensure that there were no cracks. The cut cubic specimens of Group A and Group B were median filtered and segmented using an algorithm. The appropriate threshold was selected to extract the internal void ratio, number of voids, number of isolated voids, and average volume of isolated voids after the first CT scan specimen was cut. The average void volume and isolated void ratio of the semi-cylindrical specimen after the first CT test were calculated and recorded as V1 and P1, respectively.

[0014] (4) Immediately perform room temperature curing for 24 hours on the semi-cylindrical specimen after the first CT scan, and immediately perform a second CT scan test on the semi-cylindrical specimen after curing, maintaining the same scanning parameters, placement position and scanning angle as the first CT test, to obtain the second set of CT scan data, and then use the software to use the same processing method as the first CT scan data, and use the same threshold to calculate the average void volume and isolated void ratio of the second CT scan specimen, which are recorded as V2 and P2, respectively;

[0015] (5) The self-healing effect of the emulsified asphalt cold recycled mixture with microcapsules was evaluated by using two indicators: the average void volume self-healing rate and the isolated void ratio self-healing rate. The average void volume self-healing rate and the isolated void ratio self-healing rate are denoted as H and H, respectively. V and H P , the calculation formula is shown in formula (1) and formula (2), and the H of emulsified asphalt cold recycled mixture of group A and group B is compared and analyzed. V and HP , further indicating the self-healing effect of microcapsules on emulsified asphalt cold recycled mixture;

[0016]

[0017] In the aforementioned method for evaluating the self-healing effect of emulsified asphalt cold recycled mixture with added microcapsules, in steps (3) and (4), Avizo software is used for relevant processing; in step (3), median filtering is performed on the cube specimens cut from group A and group B, and the watershed algorithm is used for segmentation.

[0018] Beneficial effects of the present invention: Compared with the prior art, the emulsified asphalt cold regeneration technology enables the resource reuse of RAP materials, which has higher social, economic and environmental benefits. The cold regeneration technology uses emulsified asphalt as a binder, and mixes it with RAP materials, cement, new materials and other materials at room temperature to form a regenerated asphalt pavement, which has the advantages of low energy consumption and convenient construction. However, ordinary emulsified asphalt has problems such as low mechanical strength and poor low-temperature crack resistance, resulting in relatively poor low-temperature crack resistance and fatigue performance of the regenerated asphalt pavement, which is not conducive to extending the service life of the asphalt pavement. The self-healing ability of cracks in the emulsified asphalt cold regenerated mixture can be improved by adding microcapsules containing regeneration agents, but the existing evaluation methods can only evaluate the self-healing effect of the cold regenerated mixture from a macroscopic perspective, and the particle size of the microcapsules belongs to the micron level of the mesoscopic scale. It is difficult to evaluate the self-healing effect of the microcapsule emulsified asphalt cold regenerated mixture at the mesoscopic scale through macroscopic experiments.

[0019] Therefore, the present invention evaluates the self-healing effect of microcapsules on emulsified asphalt cold recycled mixture from a microscopic perspective, which makes up for the limitations of macroscopic experimental analysis of the self-healing effect of asphalt mixture, and provides a new evaluation method for the self-healing effect of microcapsule emulsified asphalt cold recycled mixture. The self-healing effect of emulsified asphalt cold recycled mixture is more accurately evaluated by using the changes in the mesoscopic void characteristics of the cold recycled mixture before and after maintenance that matches the scale of the microcapsules, a more reasonable mix ratio of emulsified asphalt cold recycled mixture is designed, an emulsified asphalt cold recycled mixture with better self-healing effect is developed, and the service life of the cold recycled pavement is extended. DETAILED DESCRIPTION

[0020] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.

[0021] Embodiments of the present invention: In order to solve the problem that it is difficult to accurately evaluate the self-healing effect of cracks in microcapsule emulsified asphalt cold recycled mixtures in current macroscopic mechanical tests. The present invention proposes a method for evaluating the self-healing effect of emulsified asphalt cold recycled mixtures with added microcapsules. First, a semi-cylindrical specimen of emulsified asphalt cold recycled mixture with added microcapsules is prepared, and cracks are prefabricated by a semi-circular bending fatigue test; a CT test is performed on the cracked specimen before and after maintenance to obtain CT scanning data, and image processing is performed on the semi-cylindrical specimen after two scans, and the specimen is cut into a cubic specimen with the crack extension area in the middle of the specimen as the center to ensure that there are no cracks in the cut part; the internal void parameters of the specimens scanned twice by CT are calculated by the same processing method, and the self-healing rate of the average void volume and the isolated void ratio is used to evaluate the self-healing effect of the microcapsule emulsified asphalt cold recycled mixture.

[0022] The specific implementation steps are as follows:

[0023] (1) According to the "Test Code for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011), Marshall specimens of emulsified asphalt cold recycled mixtures, group A and group B, were prepared, wherein the microcapsule content of the Marshall specimens of group A was 0%, and the microcapsule content of the Marshall specimens of group B was 5%. Each Marshall specimen of group A and group B was cut along the direction perpendicular to the height to cut into a cylindrical specimen with a height of 50 mm, and then symmetrically cut into two semi-cylindrical specimens. A cut was made at the middle position of the bottom of the semi-cylindrical specimen, with a cut length of 5 mm and a cut width of 2 mm. Semi-cylindrical bending specimens with pre-cuts were prepared. The first semi-circular bending fatigue test was performed on some of the semi-cylindrical specimens in group A and group B under the stress ratio of 0.25, respectively, to obtain the first fatigue life of the specimens of group A and group B when loaded to complete fracture;

[0024] (2) performing a semicircular bending fatigue test on the other semi-cylindrical specimens of group A and group B respectively under the condition of a stress ratio of 0.25, controlling the fatigue life of this semi-circular bending fatigue test to be 60% of the fatigue life of the first semi-circular bending test, thereby prefabricating cracks on the semi-cylindrical bending specimens of group A and group B, and immediately performing the first CT scanning test on the semi-cylindrical specimens with prefabricated cracks to obtain the first set of CT scanning data;

[0025] (3) The scanned semi-cylindrical specimen images were cut using Avizo software and cut into cubic specimens with the crack extension area in the middle of the specimen as the center. During the cutting process, all slices of the cut part were checked to ensure that there were no cracks. The cut cubic specimens of Group A and Group B were median filtered and segmented using the watershed algorithm. The appropriate threshold was selected to extract the internal void ratio, number of voids, number of isolated voids, and average volume of isolated voids after the first CT scan specimen was cut. The average void volume and isolated void ratio of the semi-cylindrical specimen after the first CT test were calculated and recorded as V1 and P1, respectively.

[0026] (4) After the first CT scan, the semi-cylindrical specimen was immediately cured at room temperature for 24 hours, and a second CT scan test was immediately performed on the semi-cylindrical specimen after curing, with the same scanning parameters, placement position and scanning angle as the first CT test, to obtain the second set of CT scan data, and then the Avizo software was used to process the data in the same way as the first CT scan data, and the same threshold was used to calculate the average void volume and isolated void ratio of the second CT scan specimen, which were recorded as V2 and P2, respectively;

[0027] (5) The self-healing effect of the emulsified asphalt cold recycled mixture with microcapsules was evaluated by using two indicators: the average void volume self-healing rate and the isolated void ratio self-healing rate. The average void volume self-healing rate and the isolated void ratio self-healing rate are denoted as H and H, respectively. V and H P , the calculation formula is shown in formula (1) and formula (2), and the H of emulsified asphalt cold recycled mixture of group A and group B is compared and analyzed. V and H P , further demonstrating the self-healing effect of microcapsules on emulsified asphalt cold recycled mixture.

[0028]

[0029] The particle size of the commonly used road microcapsules is currently in the micron level, which is relatively small compared to the scale of the asphalt mixture itself. It is not accurate to characterize the self-healing effect of the microcapsules only by using mechanical properties tests on a macro scale. Therefore, the present invention uses a semicircular bending fatigue test to preform cracks on a semicircular bending specimen of a microcapsule emulsified asphalt cold recycled mixture, and performs curing at room temperature for 24 hours. An X-ray tomography test is used to extract the internal void characteristics of the cold recycled mixture before and after curing. The crack self-healing effect of the microcapsule emulsified asphalt cold recycled mixture is analyzed by comparing the changes in void characteristics before and after curing, providing a new idea for the evaluation of the self-healing effect of the emulsified asphalt cold recycled mixture.

Claims

1. A method for evaluating the self-healing effect of cold recycled asphalt mixture with added microcapsules, characterized in that: First, a semi-cylindrical specimen of emulsified asphalt cold recycled mixture with microcapsules added was prepared, and cracks were prefabricated using a semi-circular bending fatigue test. A CT test was carried out on the cracked specimen before and after maintenance to obtain CT scanning data. The semi-cylindrical specimen was image processed after two scans and cut into cubic specimens with the crack extension area in the middle of the specimen as the center to ensure that there were no cracks in the cut part. The internal void parameters of the specimens scanned twice by CT were calculated using the same processing method, and the self-healing effect of the microcapsule emulsified asphalt cold recycled mixture was evaluated using the self-healing rate of the average void volume and the isolated void ratio.

2. The method for evaluating the self-healing effect of cold recycled asphalt mixture with added microcapsules according to claim 1, characterized in that: The specific implementation steps are as follows: (1) Prepare Marshall specimens of emulsified asphalt cold recycled mixture, group A and group B, wherein the microcapsule content of Marshall specimens of group A is 0%, and the microcapsule content of Marshall specimens of group B is 5%. Cut each Marshall specimen of group A and group B along the direction perpendicular to the height into a cylindrical specimen, and then symmetrically cut into two semi-cylindrical specimens. Perform incision processing at the middle position of the bottom of the semi-cylindrical specimen to prepare a semi-cylindrical bending specimen with a pre-cut. Perform the first semi-circular bending fatigue test on some of the semi-cylindrical specimens in group A and group B under the stress ratio of 0.25, and obtain the first fatigue life of the specimens of group A and group B when loaded to complete fracture; (2) performing a semicircular bending fatigue test on the other semi-cylindrical specimens of group A and group B respectively under the condition of a stress ratio of 0.25, controlling the fatigue life of this semi-circular bending fatigue test to be 60% of the fatigue life of the first semi-circular bending test, thereby prefabricating cracks on the semi-cylindrical bending specimens of group A and group B, and immediately performing the first CT scanning test on the semi-cylindrical specimens with prefabricated cracks to obtain the first set of CT scanning data; (3) The scanned semi-cylindrical specimen image was cut by software, and the specimen was cut into a cubic specimen with the crack extension area in the middle of the specimen as the center. During the cutting process, all slices of the cut part were checked to ensure that there were no cracks. The cut cubic specimens of Group A and Group B were median filtered and segmented using an algorithm. The appropriate threshold was selected to extract the internal void ratio, number of voids, number of isolated voids, and average volume of isolated voids after the first CT scan specimen was cut. The average void volume and isolated void ratio of the semi-cylindrical specimen after the first CT test were calculated and recorded as V1 and P1, respectively. (4) Immediately perform room temperature curing for 24 hours on the semi-cylindrical specimen after the first CT scan, and immediately perform a second CT scan test on the semi-cylindrical specimen after curing, maintaining the same scanning parameters, placement position and scanning angle as the first CT test, to obtain the second set of CT scan data, and then use the software to use the same processing method as the first CT scan data, and use the same threshold to calculate the average void volume and isolated void ratio of the second CT scan specimen, which are recorded as V2 and P2, respectively; (5) The self-healing effect of the emulsified asphalt cold recycled mixture with microcapsules was evaluated by using two indicators: the average void volume self-healing rate and the isolated void ratio self-healing rate. The average void volume self-healing rate and the isolated void ratio self-healing rate are denoted as H and H, respectively. V and H P , the calculation formula is shown in formula (1) and formula (2), and the H of emulsified asphalt cold recycled mixture of group A and group B is compared and analyzed. V and H P , further indicating the self-healing effect of microcapsules on emulsified asphalt cold recycled mixture; 3. The method for evaluating the self-healing effect of cold recycled asphalt mixture with added microcapsules according to claim 2, characterized in that: In the steps (3) and (4), Avizo software is used for relevant processing; in the step (3), median filtering is performed on the cut cube specimens of group A and group B, and the watershed algorithm is used for segmentation.